Overlapping spheres of authority and interface conflicts in the global order: Introducing a DFG research group - Michael Zürn; Benjamin Faude; Christian Kreuder-Sonnen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
The DFG research group, "Overlapping Spheres of Authority and Interface Conflicts in the Global Order" (OSAIC), focuses on the rise of interface conflicts within and across overlapping spheres of authority. The increased institutional production of norms in the international realm leads to both horizontal interface conflicts at the same level of governance (e.g. across two or more international spheres of authority) and vertical interface conflicts across spheres of authority on different levels (e.g. international and national spheres of authority). Under which conditions become such conflicts manifest? What are the responses to conflicting rules originating from overlapping spheres of authority? To what extent are these responses guided by normative principles? If responses are justified with reference to normative principles, what are these principles and how are they operationalized concretely? What consequences do the different ways of responding to interface conflicts have for the global order as a whole? With these questions, the research group moves beyond the study of issue-area specific international institutions or organizations, and targets the question of the international order understood as a system of overlapping and interacting spheres of authority. In order to answer these questions, the research group proceeds in four steps. First, we utilize different methods for identifying such conflicts in order get a better understanding of the extent and content of interface conflicts. Second, we develop an empirically validated typology capable of grasping systematically the variety of responses to interface conflicts. Third, we use this typology as a basis for explaining variance in the responses to interface conflicts and for analyzing the consequences of different responses for the global political order. Fourth, we seek to reconstruct existing normative practices and develop standards for their evaluation. – – Die DFG Forschungsgruppe "Overlapping Spheres of Authority and Interface Conflicts in the Global Order" (OSAIC) untersucht immer häufiger auftretende Schnittstellenkonflikte innerhalb sowie zwischen überlappenden Autoritätssphären. Die angestiegene institutionelle Erzeugung von Normen in der internationalen Politik führt zum einen zu horizontalen Schnittstellenkonflikten auf dem gleichen Governance-Level (z.B. zwischen zwei oder mehreren internationalen Autoritätssphären) und zum anderen zu vertikalen Schnittstellenkonflikten zwischen Autoritätssphären auf unterschiedlichen Levels (z.B. internationale und nationale Autoritätssphären). Unter welchen Bedingungen manifestieren sich solche Konflikte? Was sind die Antworten auf sich widersprechende Regeln, die aus den sich überlappenden Autoritätssphären hervorgehen? Inwiefern sind diese Antworten von normativen Prinzipien geleitet? Falls Antworten mit Verweis auf normative Prinzipien gerechtfertigt werden, um welche Prinzipien handelt es sich dabei genau und wie lassen sie sich konkret operationalisieren? Welche Konsequenzen haben die unterschiedlichen Antworten auf Schnittstellenkonflikte für die globale Ordnung insgesamt? Durch diese Fragestellungen beschäftigt sich die Forschungsgruppe mit mehr als nur der politikfeldpezifischen Analyse internationaler Institutionen oder Organisationen. Sie zielt vielmehr auf ein Verständnis der internationalen Ordnung als System von sich überlappenden und interagierenden Autoritätsfeldern ab. Um die Fragen beantworten zu können, geht die Forschungsgruppe in vier Schritten vor. Zuerst nutzen wir verschiedene Methoden, um Konflikte dieser Art identifizieren zu können und um somit ein besseres Verständnis für das Ausmaß und den Inhalt von Schnittstellenkonflikten zu entwickeln. Im zweiten Schritt entwickeln wir eine empirisch valide Typologie, die in der Lage ist, systematisch die Vielzahl von Antworten auf diese Konflikte zu erfassen. Im dritten Schritt nutzen wir diese Typologie als Ausgangspunkt, um die Varianz der Antworten auf Schnittstellenkonflikte zu erklären und um die Konsequenzen der verschiedenen Antworten für die globale politische Ordnung zu analysieren. Zuletzt ist es unser Ziel, existierende normative Praktiken zu rekonstruieren und Standards für ihre Evaluierung zu entwickeln.
Keywords: 320; overlapping spheres of authority; interface conflicts; global order; multi-level governance; international institutions; überlappende Autoritätssphären; Schnittstellenkonflikte; globale Ordnung; Multi-Level Governance; internationale Institutionen